2010
DOI: 10.1140/epje/i2010-10611-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical determinants of vascular network remodeling during tumor growth

Abstract: The process in which a growing tumor transforms a hierarchically organized arterio-venous blood vessel network into a tumor specific vasculature is analyzed with a theoretical model. The physical determinants of this remodeling involve the morphological and hydrodynamic properties of the initial network, generation of new vessels (sprouting angiogenesis), vessel dilation (circumferential growth), vessel regression, tumor cell proliferation and death, and the interdependence of these processes via spatio-tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 44 publications
3
70
0
Order By: Relevance
“…The J-PET detector [1][2][3][4][5][6] being developed at Jagiellonian University is a Positron Emission Tomograph composed of long strips of polymer scintillators. One among the major goals of present research of the J-PET collaboration is to find an optimal reconstruction method to estimate gamma quanta hit time and hit position which would allow to make use of the very good time resolution achievable with plastic scintillators.…”
Section: Faculty Of Physics Astronomy and Applied Computer Science Jmentioning
confidence: 99%
See 2 more Smart Citations
“…The J-PET detector [1][2][3][4][5][6] being developed at Jagiellonian University is a Positron Emission Tomograph composed of long strips of polymer scintillators. One among the major goals of present research of the J-PET collaboration is to find an optimal reconstruction method to estimate gamma quanta hit time and hit position which would allow to make use of the very good time resolution achievable with plastic scintillators.…”
Section: Faculty Of Physics Astronomy and Applied Computer Science Jmentioning
confidence: 99%
“…When combined, flocking and the SIR epidemic model constitute a representation of how a disease might spread through a large group of animals. This paper talks about the first simulation of the model using libGDX -a Java-based framework for game development [3,4]. It includes a graphical representation of the population, along with a menu, which enables the user to adjust the parameters of the simulation, allowing for a close examination of the system.…”
Section: School Of Informatics University Of Edinburgh United Kingdommentioning
confidence: 99%
See 1 more Smart Citation
“…31 Up to the angiogenic shift (that does not necessarily happens) the tumor is referred to as in a dormant phase. The tumor is generally believed to remain in the dormant phase up to a size of 1mm; the…”
Section: Cancermentioning
confidence: 99%
“…Percolation has also been used to represent the vascular network of tumors and normal tissues. Baish et al [52] and Welter and Rieger [53] found that when percolation was incorporated, the delivery of blood-borne molecules and nanoparticles in the tumor and tissue were dependent on the differences in their vascular architectures. However, they did not compare the differences in the homogeneity of the tissues surrounding a tumor.…”
Section: Introductionmentioning
confidence: 99%